FREQUENCY, PATTERN AND ETIOLOGY OF NOSOCOMIAL INFECTION IN INTENSIVE CARE UNIT: AN EXPERIENCE AT A TERTIARY CARE HOSPITAL - Shaikh, Jan Muhammad; Devrajani, Bikha Ram; Shah, Syed Zulfiquar Ali; Akhund, Tauseefullah; Bibi, Ishrat (Journal of Ayub Medical College Abbottabad, 2008)
Background: Nosocomial infection is defined as an infection which develops 48 hours after hospital admission or within 48 hours after being discharged. The objectives were to assess the frequency of nosocomial infection in patients admitted to intensive care unit (ICU) and to determine the etiological factors in such patients. It was an Observational Study and conducted in Intensive Care Unit, Liaquat University Hospital Hyderabad Sindh Pakistan from January 2008 to November 2008. Methods: All patients above 16 years of age admitted in the ICU for more than 48 hours and developed clinical evidence of infection that did not originate from patients’ original diagnosis at the time of admission, were included in the study. Data was entered in a proforma and analyzed using SPSS version 10.0. Results: During the study period, 97 out of 333 patients acquired nosocomial infection. The frequency of nosocomial infection was 29.13%. Respiratory tract infection was seen in 29 (30.1%), urinary tract infection in 38 (39.1%) and blood stream infection in 23 (23.7%) patients. Other infections we identified were skin, soft tissue, wound and gastrointestinal tract infections. Conclusion: Patients admitted in intensive care unit are at more risk of acquiring nosocomial infection from different sources. It is suggested that proper nursing care, sterilization and disinfection of instruments and equipment and careful handling of invasive procedures are the best tool to control these life threatening infections. Keywords: intensive care unit, Nosocomial infection, Hospital acquired infection